(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Toponyms (place names) represent language units denoting elements of topographic environment. The relevance of the study is caused by the need to develop the theory of toponymy and to systematize all the existing toponymic classifications. Place names have a complicated (multidimensional) nature, which should be taken into account while classifying them. This research is an attempt to highlight various principles according to which it is possible to group the place names. This article is based on 15000 British and 17000 American toponyms, received from toponymic dictionaries, reference books and electronic toponymic search systems GNIS (Geographic Names Information System) and Get-a-map.